Preparation of Cod Gelatin Antifreeze Peptides and Its Application of Frozen-Thawed Surimi - Jin ZHANG; Tao YUAN; Xiaomei SHA; Yuelun XU; Yating KUANG; Zizi HU (Shipin gongye ke-ji)
To optimize the preparation method of highly active cod gelatin antifreeze peptides (DcAFPs) and clarify its cryoprotective effects on surimi, this study added cod gelatin peptides to surimi. The myofibrillar protein content in the surimi after freezing was used as an evaluation index, and the process was optimized through single-factor and orthogonal experiments. By determining the molecular weight distribution and amino acid composition of DcAFPs, their basic properties were analyzed. Additionally, the protective effects of DcAFPs on surimi subjected to repeated freeze-thaw cycles were assessed by measuring myofibrillar protein content and utilizing intrinsic fluorescence spectroscopy and SDS-PAGE gel electrophoresis techniques. The results showed that the optimal preparation process for DcAFPs involved using compound protease, with a substrate concentration of 3.5% (w/v), an enzyme-to-substrate ratio of 5% (w/w), a hydrolysis pH of 8, a hydrolysis temperature of 55 ℃, and a hydrolysis time of 2 hours. The molecular weight of DcAFPs was primarily concentrated between 185 and 3081 Da, with glycine (Gly), alanine (Ala), and glutamic acid (Glu) being the most abundant amino acids. DcAFPs effectively prevented the reduction of myofibrillar protein content during freeze-thaw cycles, inhibited changes in the structure and composition of myofibrillar proteins, and delayed protein denaturation. In conclusion, DcAFPs exhibited significant cryoprotective effects on surimi that subjected to repeated freeze-thaw cycles and outperformed commercial antifreeze agents.